Influence of Lanthanum(III) Dopant on Structure, Linear and Non-Linear Optical Properties of Ammonium Pentaborate Crystals - MUNIRATHNAM*, B.; MADHAVAN†, J. (Asian Journal of Chemistry, 2024)
Single crystals of pure and lanthanum doped ammonium pentaborate (AB5) have been successfully grown from aqueous solution by slow evaporation technique. The growth conditions of both pure and La3+ doped AB5 are optimized and the grown crystals are investigated by powder X-Ray diffraction technique. The grown crystals of pure and La3+ doped AB5 are subjected to FT-IR and UV-Vis-NIR spectral techniques and the influences of La3+ are reported. The second harmonic generation of the crystals was confirmed by Kurtz and Perry powder technique and the influence of La3+ is also discussed.